Measurement the Spectroscopic Temperature of Electron in Aluminum Laser Induced Plasma - Abdulameer, Mohammed R (Al-Nahrain Journal of Science, 2017)
In this research, optical emission spectroscopic studies have been carried out in Aluminum plasma generated using 1064nm, 10ns pulses from Nd:YAG laser. Temperature was estimated from the analysis of spectral data. The temperature values measurements have been performed by the comparison of two selected spectral lines of the radiation emitted by laser induced plasma of Al using singly ionized Al atom and neutral lines. An initial temperature of 2.6 eV was measured. The relation between electron temperature and laser pulse energy in the laser-generated Al plasma have been analyzed. The electron temperatures values are found to increase from 2.6 eV to 2.8 eV then to 2.9 eV as increasing laser pulse energy